High frequency of Panton-Valentine leukocidin in Staphylococcus aureus causing pediatric infections in the city of Cartagena-Colombia - Oscar Correa-Jiménez; Hernando Pinzón-Redondo; Niradiz Reyes (Elsevier, 2016)
Summary: Panton-Valentine leucocidin (PVL) is a pore-forming toxin that has been epidemiologically associated with CA-MRSA infections. However, its role in the pathogenicity of Staphylococcus aureus is still unclear. We evaluated the prevalence of PVL-coding genes in methicillin-resistant (MRSA) and methicillin-sensitive (MSSA) isolates that cause infections in pediatric patients in the city of Cartagena, Colombia. We obtained S. aureus isolates from patients at the Napoleon Franco Pareja Children's Hospital in Cartagena. Then, we evaluated the presence of the nuc, mecA, and PVL genes in these isolates by multiplex PCR and determined the antibiotic susceptibility profiles using CLSI standards. We further correlated methicillin susceptibility and the presence of PVL genes with clinical variables. Overall PVL prevalence in S. aureus isolates was 73.91%, with a frequency of 80.92% among MRSA isolates and 67.59% among MSSA. We found a correlation between erythromycin resistance and lack of PVL and found that PVL+ cases were more common in older patients. We found a high PVL prevalence in both MRSA and MSSA isolates, in concordance with previous regional reports. Keywords: Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus, Bacterial Toxins, Pathogenicity, Virulence factors, Panton-Valentine leukocidin, Pediatrics